Mengurai Dinamika Ras dan Etnisitas dalam Ruang Pendidikan Multikultural: Studi Kualitatif di Sekolah Menengah - Irfan Arif Nugroho; Ar-Rizky Maulana Akbar; Radhi Fakhri Yuwono (Politeknik Kampar, 2025)
This study aims to reveal the dynamics of relations between ethnic groups in the context of multicultural secondary education in Indonesia. This qualitative study was conducted through a case study approach in one of the state schools in West Java that has high ethnic diversity. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using thematic analysis. The results of the study indicate complex interactions between students from various ethnic backgrounds, which reflect both processes of integration and social exclusion. Several social mechanisms such as stereotypes, cultural segregation, and majority dominance structures were identified as factors shaping these dynamics. These findings indicate the need for a more multiculturalist-aware educational approach and school policy interventions that promote racial and ethnic justice.